2016
DOI: 10.1007/s11894-016-0508-y
|View full text |Cite
|
Sign up to set email alerts
|

Virologic Cure of Hepatitis C: Impact on Hepatic Fibrosis and Patient Outcomes

Abstract: Treatment with direct-acting antiviral agents has revolutionized the approach to hepatitis C. We are now able to obtain high sustained virological response (SVR) rates, even in the historically difficult-to-treat patient populations. SVR translates into improved clinical outcomes, particularly overall and liver-related mortality, and benefits are more striking in patients with cirrhosis. A 2.5- to 5-fold risk reduction in the incidence of hepatocellular carcinoma and improvement in complications derived from p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 78 publications
0
14
0
Order By: Relevance
“…A Taiwanese study in the nontransplant population concluded that SVR significantly improved renal outcomes . SVR has been associated with a decreased incidence of ESRD as well as LT‐related mortality and development of hepatocellular carcinoma . As such, the beneficial effects of AVT may now be extended to its potential renal protective effect in the posttransplant setting.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A Taiwanese study in the nontransplant population concluded that SVR significantly improved renal outcomes . SVR has been associated with a decreased incidence of ESRD as well as LT‐related mortality and development of hepatocellular carcinoma . As such, the beneficial effects of AVT may now be extended to its potential renal protective effect in the posttransplant setting.…”
Section: Discussionmentioning
confidence: 99%
“…(24,25) SVR has been associated with a decreased incidence of ESRD (24) as well as LT-related mortality and development of hepatocellular carcinoma. (26)(27)(28) As such, the beneficial effects of AVT may now be extended to its potential renal protective effect in the posttransplant setting. HCV infection induces kidney injury, mostly due to the formation of immune complexes and cryoglobulins, and possibly to a direct cytopathic effect.…”
Section: Discussionmentioning
confidence: 99%
“…Although the mechanism underlying this decrease in-risk is yet to be fully determined, there is agreement that fibrosis regression plays a pivotal role 1. SVR has been considered the goal of HCV treatment; however, liver fibrosis rather than serum viremia is the most important prognostic factor in chronic HCV patients 30…”
Section: Discussionmentioning
confidence: 99%
“…The majority of affected individuals develop a chronic infection, and approximately 30% of them will progress to cirrhosis within 20–30 years following infection. Therefore, HCV is a leading cause of end-stage liver disease and hepatocellular carcinoma (HCC) 14. However, it has been proven that effective antiviral treatment modifies the natural history of chronic HCV, reduces fibrosis and decreases the subsequent HCV-related complications and mortality 1,57…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the heterogeneous surveillance intervals in reports using liver stiffness measurements, the durations were significantly shorter either during treatment or between the end of treatment (EOT) and follow-up in patients with CHB and CHC than those reported in histological studies with follow-up periods of up to 10 years [24,25]. Studies applying paired liver biopsies (pre-and post-antiviral treatment) have reported rates of cirrhosis reversal of up to 74% of patients with CHB and 18-64% of patients with CHC with cirrhosis over long-term intervals of up to 5 and 10 years, respectively [9,[24][25][26]. Nonetheless, the paradigms of liver stiffness measurements have shifted focus from the outdated cross-sectional liver fibrosis staging alone to comprehensive liver-relevant risk estimation [27].…”
Section: Introductionmentioning
confidence: 86%